2007
DOI: 10.1080/10489220701600457
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Investigation of Processing Costs in Implicature Production

Abstract: Much developmental work has been devoted to scalar implicatures. These are implicitly communicated propositions linked to relatively weak terms (consider how Some pragmatically implies Not all) that are more likely to be carried out by adults than by children. Children tend to retain the linguistically encoded meaning of these terms (wherein Some is compatible with All). In three experiments, we gauge children's performance with scalars while investigating four factors that can have an effect on implicature pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
179
5
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(209 citation statements)
references
References 33 publications
21
179
5
4
Order By: Relevance
“…Besides showing that children have difficulty generating relevant alternatives for scales like some, all , these data also suggest that, contrary to speculation in the literature (e.g., Chierchia et al 2001;Pouscoulous et al 2007;Reinhart 2004), children's difficulties are not straightforwardly attributable to limitations of working memory, task demand, or other types of processing constraints. In our study, we found that children were perfectly capable of deriving strengthened interpretations for utterances that involved contextual alternatives, but failed for identical sentences that involved some.…”
Section: General Discussion and Conclusioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Besides showing that children have difficulty generating relevant alternatives for scales like some, all , these data also suggest that, contrary to speculation in the literature (e.g., Chierchia et al 2001;Pouscoulous et al 2007;Reinhart 2004), children's difficulties are not straightforwardly attributable to limitations of working memory, task demand, or other types of processing constraints. In our study, we found that children were perfectly capable of deriving strengthened interpretations for utterances that involved contextual alternatives, but failed for identical sentences that involved some.…”
Section: General Discussion and Conclusioncontrasting
confidence: 46%
“…Previous studies have suggested various factors that might affect children's derivation of implicatures, including limitations on working memory, limited understanding of context and meta-linguistic tasks, and the salience or availability of relevant scalar alternatives (see Chierchia et al 2001;Musolino 2006;Musolino & Lidz 2006;Papafragou 2006;Papafragou & Musolino 2003;Papafragou & Tantalou, 2002;Pouscoulous et al 2007). According to Papafragou and Musolino, since each of these factors might limit children's computation of implicatures, and since children readily assign exact interpretations to numerals, children must not be using implicatures to derive exact meanings of numerals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When presented with underinformative sentences like ''Some giraffes have long necks'', 89% of the children in Noveck's study answered that this statement is true (logical/literal interpretation), while only 41% of the adults responded true. Other developmental studies have confirmed the finding that children do not derive scalar implicatures to the same extent as adults do, even when given more explicit instructions, a training session or acting out tasks that do not require real world knowledge and which are easier for children (Guasti et al 2005;Papafragou and Musolino 2003;Pouscoulous et al 2007). The finding that children's performance improved when manipulating experimental conditions, suggests that it is not merely pragmatic competence as such that is lacking in children, and that limited cognitive resources may be part of the explanation.…”
Section: Scalar Implicaturesmentioning
confidence: 77%